Gestational Diabetes and Peptides in Breast Milk - Aydin, Suleyman (Palgrave Macmillan, 2018)
Maternal milk contains many small peptides that are involved in the regulation of infant’s metabolism. The alteration in the amount of the peptides/proteins in maternal milk may decide the fate of metabolic events programmed by birth to unfold in a harmonious way and mediate the development of some metabolic diseases in later years of life. Thus, this chapter was to describe how the fate of hormones in breast milk changes in gestational diabetes, and what the effects of these changes on mothers and their offspring are or can be. © Springer International Publishing AG 2018.
Keywords: Baby; Breast milk; Gestational diabetes; Metabolic balance; Nutrition; Peptides